2017
DOI: 10.19082/5770
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combined sertraline and aspirin therapy on depression severity among patients with major depressive disorder: A randomized clinical trial

Abstract: BackgroundDifferent studies have been conducted to find the best adjuvant therapies for depression management. There are controversies over the effects of aspirin as an adjuvant therapy for depression.ObjectiveTo determine the effects of combined sertraline and aspirin therapy on depression severity among patients with major depressive disorder.MethodsThis randomized clinical trial was conducted at Kargarnejad Psychiatric Hospital in Kashan, Isfahan, Iran, from September 1, 2016 to November 1, 2016. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…After screening titles/abstracts and removing duplicate studies, the full texts of 364 potentially eligible studies were obtained. Ultimately, 39 randomized clinical trials ( Akhondzadeh et al, 2009 ; Abbasi et al, 2012 ; da Silva et al, 2008 ; Krause et al, 2017 ; Majd et al, 2015 ; Müller et al, 2006 ; Sepehrmanesh et al, 2017 ; Arana et al, 1995 ; DeBattista et al, 2000 ; Otte et al, 2010 ; Ghanizadeh and Hedayati, 2013 ; Gougol et al, 2015 ; Haghighi et al, 2014 ; Rasgon et al, 2016 ; Sepanjnia et al, 2012 ; Dean et al, 2017 ; Emadi-Kouchak et al, 2016 ; Husain et al, 2017 ; Berk et al, 2014 ; Bot et al, 2010 ; Carney et al, 2009 ; Carney et al, 2019 ; Chang et al, 2020 ; Gertsik, 2012 ; Grenyer et al, 2007 ; Jahangard et al, 2018 ; Jazayeri et al, 2008 ; Jiang et al, 2018 ; Keshavarz et al, 2018 ; Lespérance et al, 2011 ; Marangell et al, 2003 ; Mischoulon et al, 2009 ; Mischoulon et al, 2015 ; Nemets et al, 2002 ; Park et al, 2015 ; Rapaport et al, 2016 ; Rondanelli et al, 2010 ; Shinto et al, 2016 ; Su et al, 2003 ) were included in the quantitative data synthesis. Figure 1 illustrates the systematic literature searching and study selection processes.…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles/abstracts and removing duplicate studies, the full texts of 364 potentially eligible studies were obtained. Ultimately, 39 randomized clinical trials ( Akhondzadeh et al, 2009 ; Abbasi et al, 2012 ; da Silva et al, 2008 ; Krause et al, 2017 ; Majd et al, 2015 ; Müller et al, 2006 ; Sepehrmanesh et al, 2017 ; Arana et al, 1995 ; DeBattista et al, 2000 ; Otte et al, 2010 ; Ghanizadeh and Hedayati, 2013 ; Gougol et al, 2015 ; Haghighi et al, 2014 ; Rasgon et al, 2016 ; Sepanjnia et al, 2012 ; Dean et al, 2017 ; Emadi-Kouchak et al, 2016 ; Husain et al, 2017 ; Berk et al, 2014 ; Bot et al, 2010 ; Carney et al, 2009 ; Carney et al, 2019 ; Chang et al, 2020 ; Gertsik, 2012 ; Grenyer et al, 2007 ; Jahangard et al, 2018 ; Jazayeri et al, 2008 ; Jiang et al, 2018 ; Keshavarz et al, 2018 ; Lespérance et al, 2011 ; Marangell et al, 2003 ; Mischoulon et al, 2009 ; Mischoulon et al, 2015 ; Nemets et al, 2002 ; Park et al, 2015 ; Rapaport et al, 2016 ; Rondanelli et al, 2010 ; Shinto et al, 2016 ; Su et al, 2003 ) were included in the quantitative data synthesis. Figure 1 illustrates the systematic literature searching and study selection processes.…”
Section: Resultsmentioning
confidence: 99%
“…ASA has also been studied in depression. In an 8-week RCT in MD, patients were assigned to 160 mg of aspirin add-on to sertraline ( n = 50) or placebo add-on ( n = 50); the groups were matched for age, gender, and severity of depression (23). After 4 and 8 weeks of treatment, depression scores were significantly lower than at baseline only in the sertraline plus aspirin group.…”
Section: Major Depressionmentioning
confidence: 99%
“…While there are positive randomised controlled trials of statins for the treatment of depression [32][33][34], and meta-analytic evidence for their effectiveness [35], no studies have investigated their therapeutic potential among youth. A pilot study comparing low-dose aspirin added to sertraline with sertraline alone found that the former was superior on the Beck Depression Inventory at the trial endpoint [36].…”
Section: Introductionmentioning
confidence: 99%